ANOMALOUS OCEANIC CONDITIONS IN THE TROPICAL INDIAN OCEAN DURING 2006 AS REVEALED BY MULTI-SATELLITE SENSORS - Iskandar, Iskhaq (Marine Research in Indonesia, 2009)
A positive Indian Ocean Dipole (IOD) took place in the tropical Indian Ocean during 2006. The evolution of this event started in July 2006 and intensified during August 2006. It was indicated by negative sea surface temperature anomalies, lower than normal sea level and supressed convection in the southeastern equatorial Indian Ocean in contrast to western counterpart. Peak negative SST anomalies exceeding 1Â°C were observed in the eastern basin during September-November coinciding with anomaous easterly winds along the equator and strong southeasterly winds along the coast of Sumatra and Java. The expression of this positive IOD was also seen in other physical variables: negative sea surface height anomalies about 30 cm and negative rainfall anomalies exceeding 8 mm/day were observed in the eastern basin. The events was terminated in December 2006 mainly due to warming of the eastern pole. The magnitude of this event determined by the east-west temperature gradient across the tropical Indian Ocean was the third largest in the last 30 years, after 1997 and 1994 events.